2018
DOI: 10.7498/aps.67.20181033
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic parameters of optical wave and short-term beam spreading in oceanic turbulence

Abstract: In 2000, Nikishov et al. presented an analytical model for the power spectrum of oceanic turbulence, in which the stable stratification of seawater is assumed, i.e., the eddy diffusivity of temperature is equal to that of salinity, and the eddy diffusivity ratio is equal to unity. Until now, all previous studies on the light propagation through oceanic turbulence were based on the Nikishov's power spectrum model. However, the eddy diffusivity of temperature and eddy diffusivity of salt are different from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…[15] On the other hand, it can be found that partially coherent beams have advantage over fully coherent beams for mitigating the effect of turbulence. [16] The evolution properties of various partially coherent beams propagating in oceanic turbulent were discussed, such as partially coherent flat-topped vortex hollow beam, [17] partially coherent Lorentz-Gauss beam, [18] partially coherent Lorentz-Gauss vortex beam, [19] stochastic beams, [20] astigmatic stochastic electromagnetic beam, [21] partially coherent four-petal Gaussian beam, [22] partially coherent four-petal Gaussian vortex beam, [23] partially coherent Hermite-Gaussian linear ar-ray beam, [24] radial phase-locked partially coherent Lorentz-Gauss array beam, [25] radial phase-locked partially coherent standard Hermite-Gaussian beam, [26] phase-locked partially coherent radial flat-topped array laser beam, [27] Gaussian Schell-model vortex beam, [28] stochastic electromagnetic vortex beam, [29] partially coherent anomalous hollow vortex beam, [30] multi-Gaussian Schell-model beam, [31] rectangular multi-Gaussian Schell-model beam, [32] electromagnetic multi-Gaussian Schell-model beams with astigmatic aberration, [33] stochastic electromagnetic higher-order Bessel-Gaussian beam, [34] optical wave and short-term beam, [35] and random electromagnetic multi-Gaussian Schellmodel vortex beam. [36] The beams generated by the multi-Gaussian Schell-model (MGSM) source can evolve into the flat-topped beam as the propagation distance increases.…”
Section: Introductionmentioning
confidence: 99%
“…[15] On the other hand, it can be found that partially coherent beams have advantage over fully coherent beams for mitigating the effect of turbulence. [16] The evolution properties of various partially coherent beams propagating in oceanic turbulent were discussed, such as partially coherent flat-topped vortex hollow beam, [17] partially coherent Lorentz-Gauss beam, [18] partially coherent Lorentz-Gauss vortex beam, [19] stochastic beams, [20] astigmatic stochastic electromagnetic beam, [21] partially coherent four-petal Gaussian beam, [22] partially coherent four-petal Gaussian vortex beam, [23] partially coherent Hermite-Gaussian linear ar-ray beam, [24] radial phase-locked partially coherent Lorentz-Gauss array beam, [25] radial phase-locked partially coherent standard Hermite-Gaussian beam, [26] phase-locked partially coherent radial flat-topped array laser beam, [27] Gaussian Schell-model vortex beam, [28] stochastic electromagnetic vortex beam, [29] partially coherent anomalous hollow vortex beam, [30] multi-Gaussian Schell-model beam, [31] rectangular multi-Gaussian Schell-model beam, [32] electromagnetic multi-Gaussian Schell-model beams with astigmatic aberration, [33] stochastic electromagnetic higher-order Bessel-Gaussian beam, [34] optical wave and short-term beam, [35] and random electromagnetic multi-Gaussian Schellmodel vortex beam. [36] The beams generated by the multi-Gaussian Schell-model (MGSM) source can evolve into the flat-topped beam as the propagation distance increases.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, if an F T of more than 1dB is chosen, n(I T ) decreases with increasing D. To achieve the same n(I T ) , the required F T value decreases with an increase in D, consistent with the previous studies. [19][20][21][22] For example, to achieve the n(I T ) of 100, F T of 4.3, 6.1, 8.1 and 9 dB are required for D = 0, 1, 3 and 5 mm for plane wave, respectively, where it reduces to 2.8, 4, 5.1 and 5.5 dB, for D = 0, 1, 3 and 5 mm for spherical wave, respectively. This means that under the same oceanic turbulence and system parameters, the UOC system with spherical wave has the lower requirement for F T than that with plane wave.…”
Section: Resultsmentioning
confidence: 99%